Risperidone induced tardive dyskinesia - Kolanchinathan, Elakkya; Harichandran, Dhanya Thirookaran; Balakrishnan, Sujatha Mangattuvalappil (International Journal of Basic & Clinical Pharmacology, 2021)
Risperidone is an atypical antipsychotic drug which has been less likely to produce extrapyramidal symptoms. The aim of this case report is to illustrate that low dose risperidone may cause tardive dyskinesia. A 29 year old male patient with 9 year history of paranoid schizophrenia, developed tardive dyskinesia after receiving risperidone 2 mg for 7 years. He had received small dosages of Haloperidol before the therapy of risperidone for short periods.